Modeling and Simulation of Satellite Attitude Dynamics and Control System using Modelica - Liu, Y H; Shangguan, D S; Yao, J; Chen, L P; Ding, J W (Journal of physics. Conference series, 2019)
The control of attitude of a satellite is difficult to verify since several subsystems of different disciplines, e.g., flexible multibody dynamics, machines, electronics and control, are involved and strongly coupled. A traditional method is to model each single discipline subsystem with a domain specific software, and combine them through interfaces. However, the problems are that lots of interfaces between software have to be developed, and manual decoupling of systems should be considered during modelling process. In this Paper, models of the dynamics and the control system are established in a unified modelling software, MWorks, which is an Integrated Development Environment of Modelica. The model can be used to verify the satellite control strategy, and also provide an effective means for satellite attitude control system design. Moreover, on this basis, the whole satellite was modelled to access state parameters changes under the coupling of the dynamic subsystem, the attitude control subsystem, the power supply subsystem, the propulsion subsystem and the integrated electronic subsystem can be synthetically considered.